DAMPAK AUDIT OPERASIONAL ATAS KINERJA KARYAWAN PADA PT. PETROKIMIA GRESIK - Permadi, Noviandi Satrio; Ardini, Lilis (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is meant to find out how the implementation of human resources audit is, how the effectiveness of theperformance of employees is, how the system of performance measurement in a company is, and to find out the roleof human resource audit in increasing the effectiveness of the performance of employee at PT. Petrokimia Gresik. Thecompany has encountered some problems in the appraisal system of the performance of employee which has animplication to the performance of the company.The research type used is descriptive with qualitative approach. Thedescriptive research is conducted with the purpose to provide accurate description about the condition or certainsymptom in order to determine the correlation between one symptom and other symptoms. Meanwhile, thequalitative approach is one of the approaches which is conducted by using written data, the result of interview, thephenomena which has occurred and knowledge. The process of this research is focused on thought, comprehension,and research perception.The result of this research shows that PT. Petrokimia Gresik has implemented the controlactivity of human resources which is optimal and efficient. In appraising the performance of the employees, the 360degrees assessment method has not effective yet. By conducting, the value weighting system in the 360 degreesassessment method, the company can do their production more effective and efficient.Keywords : Human resources, performance measurement, 360 degrees system, operational audit.